2012
DOI: 10.5923/j.plant.20120202.07
|View full text |Cite
|
Sign up to set email alerts
|

Application of Rainfall-Potential Evapotranspiration Model for Determining Optimum Planting Date of Yam <i>(Dioscorea rotundata</i>) in a Tropical Wet-and-Dry Climate

Abstract: The application of Rainfall-Potential evapotranspiration (P-PE) model to yam (Dioscorea rotundata) Production was carried out in an on-farm yam trial during the 2006-2007 and 2007-2008 cropping seasons in Abeokuta, South western Nigeria. The experiment was a 3 x 2 factorial arrangement of three varieties of yam (Efuru, Ise-osi and Oniyere), two planting dates (early and late). The resulting 6 treatments were replicated three times with 14 mounds in each plot, in randomized complete block design. The general m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Although reasons for this could not be identified it can be assumed that the late planting was a major contributor to low yields. Eruola et al (2012) reported lower yields in two consecutive years from later planted yams compared with earlier planted yams at Abeokuta, a site not far from Ibadan. For water yam (D. alata L.) Marcos et al (2011) found lowest yields from latest plantings.…”
Section: Yam Yield and Soil Chemical Properties And Planting Datementioning
confidence: 88%
“…Although reasons for this could not be identified it can be assumed that the late planting was a major contributor to low yields. Eruola et al (2012) reported lower yields in two consecutive years from later planted yams compared with earlier planted yams at Abeokuta, a site not far from Ibadan. For water yam (D. alata L.) Marcos et al (2011) found lowest yields from latest plantings.…”
Section: Yam Yield and Soil Chemical Properties And Planting Datementioning
confidence: 88%
“…Another issue with early planting, especially at the beginning of the rainy season, is the probability of having a poor crop establishment if the rains are irregular. Dry spells during the early growth stages of yam have led to low ware yam production in many yam-growing areas of Nigeria (Eruola et al, 2012). Late planting may result in reduced crop duration and tuber yield.…”
Section: Introductionmentioning
confidence: 99%
“…The variability of moisture-based agro-meteorological indices is the most important element for yam production in the humid tropics [17] . For instance, late onset of rain, dry spells after planting, sprouting and the emergence of yam crop limit leaf development hence, leaf area index (LAI) and the affect tuber bulking period which largely determines tuber yield in yam [17] .…”
Section: Yam Production and Rainfall Effectiveness Indicesmentioning
confidence: 99%